Low quality-effective demand - Kari Eika (University of Oslo, Department of Economics, 2003)
Sub-standard quality is a recurrent problem within parts of the human services - in the care for frail elderly, mentally ill, the intellectually disabled, and children in need - and within law enforcement. Service quality is of great concern to the individual, and the larger society. If so important, why then is it so difficult to attain? I address this issue introducing the notion of low quality-effective demand (QED). Low QED is signified either by asymmetric information or weak consumer sovereignty, or a combination. In the standard principal-agent problem the principal may have poor information about the service quality that the agent provides, but has full incentives to monitor. With weak consumer sovereignty the service recipient cannot function as the principal, lacking the ability or the authority to monitor quality. With the U.S. nursing home sector as one particular case, I demonstrate how a better understanding of weak consumer sovereignty and low QED is important to improve the problematic quality of the human services.
Keywords: K40; L15; 330; Human services; law enforcement; service quality; Sozialstaat; Dienstleistungsqualität; Kosten-Nutzen-Analyse